Relationship between Anterior Cruciate Ligament Thickness and Intercondylar Distance in Magnetic Resonance Imaging - Paudel, Nabin; Ghimire, Prasanna; Jha, Amit; Ranabhat, Roshani; Jha, Sushmita; Singh, Avinash Kumar; Subedi, Shreya (Journal of Nepalgunj Medical College, 2025)
Introduction: The anterior cruciate ligament is crucial for maintaining knee biomechanics. It attaches proximally to the posteromedial aspect of the lateral femoral condyle and distally to the anterior intercondylar region. Intrinsic factors such as a narrow femoral intercondylar distance and a small notch width index increase the risk of its injury. A narrow notch often corresponds to a thinner, weaker anterior cruciate ligament, making it more prone to rupture. Identifying individuals with smaller intercondylar distances may help implement preventive strategies during sports and physical activities. Aims: To determine the relationship between anterior cruciate ligament thickness and intercondylar distance of the knee on Magnetic Resonance Imaging. Methods: This hospital-based, cross-sectional study was conducted with a total of 57 patients undergoing knee Magnetic Resonance Imaging for various indications. Data were analyzed using statistical package for social sciences version 26, applying Pearson’s correlation coefficient with a 5% significance level (p ≤ 0.05). Results: Of 57 patients (24 males, 33 females; mean age 40.6 years), 31 were of the right knee and 26 of the left. The mean intercondylar distance was 19.43 mm, while mean mediolateral and anteroposterior anterior cruciate ligament thicknesses were 4.60 mm and 4.76 mm, respectively. Males showed slightly larger values than females, but the differences were not statistically significant. A strong positive correlation was found between intercondylar distance and both mediolateral (r = 0.79, p < 0.001) and anteroposterior (r = 0.78, p < 0.001) anterior cruciate ligament thickness. Conclusion: The study demonstrated a significant positive correlation between anterior cruciate ligament thickness and intercondylar distance, with no significant gender difference. Wider intercondylar distances are associated with thicker anterior cruciate ligaments, indicating anatomical variation may influence ligament strength and injury risk.